Modified Clay Supported Ferrioxalate Catalysts For The Degradation Of Phenol, 4-Nitrophenol And Amoxicillin Using Photo-Fenton Process - Bolarinwa, Ayodele Olumide (2012)
As part of effort to ensure clean, less polluted water matrix and to ensure sustainable environment, three different types of naturally abundant clay were modified as heterogeneous catalyst support for the degradation of phenol, 4-nitrophenol (4-NP) and amoxicillin (AMX) in a batch Fenton process irradiated with ultra violet light. Acid treatment and metal pillaring techniques were used to modify kaolin and smectite (montmorrilinite and bentonite) clay samples, respectively.